Construction of Structural Model for Strategic Foresighting and Public Policy - Ahmed Lari, Fatma; Darwish Abdulla Lari, Mohamed Ahmed (International Journal of Sustainable Construction Engineering and Technology, 2020)
This study was intended to establish a relationship between the strategic foresight dimensions with the public policy attributes of the United Arab Emirates (UAE) government. The data was collected through questionnaire survey staffs of UAE government organizations. A total of 397 valid responses were collected and analysed. The collected data was used to develop the relationship using AMOS software. It was found that the measurement model has fulfilled or achieved all the required criteria. For structural model evaluation, it found that the model has achieved all the set criteria of the evaluation. Results of the structural model evaluation found that strategic foresight influence 69 % of the public policy making. It also found that the model has the significant relationship between strategic foresight dimensions and public policy. It was found that the model has 47% predictive relevancy. This result indicates that there is a substantial and direct effect between the strategic foresight and public policy. Hypothesis testing was conducted on the model and found that there is a significant relationship between strategic foresight dimensions and public policy is achieved. This indicates that the model can be applicable to UAE authority and contributes to the body of knowledge for further research.